OBSERVAÇÕES ECOLÓGICAS SOBRE A FORMIGA LAVA-PÉ, Solenopsis invicta BUREN, 1972 (HYMENOPTERA: FORMICIDAE) - Williams, R. N.; Menezes, M. de; Allen, G. E.; Buren, W. F.; Whitcomb, W. H. (REVISTA DE AGRICULTURA, 2015)
OBSERVAÇÕES ECOLÓGICAS SOBRE A FORMIGA LAVA-PÉ, Solenopsis invicta BUREN, 1972 (HYMENOPTERA: FORMICIDAE)